Trends and potential expansions in the environmental histories of British Malaya - Lee, Joanna W. C. (History compass, 2018)
The field of environmental history has been incredibly useful in further understanding the British Empire. Studies of Empire have explored a myriad of areas and intellectual themes, these encompassing political, material, and cultural environmental histories. Nonetheless, new trends in the field have yet to be applied to the region of British Malaya, where issues of colonial development such as those pertaining to cash crops, mining, and forestry remain the primary focus. The study of cultural environmental history, or how nature has been represented in various media, remains under-explored. Given the potential of British Malaya in contributing to cultural environmental history and vice versa, the following article provides an overview of British Malayan environmental historiography and suggests a number of ways in which it can be expanded. Additionally, it offers a brief example of how texts such as historical novels might be read as an alternative source.